1103. Respiratory Virus Infections In Solid Organ Transplant Recipients: A Single Center Experience. (31st December 2020) - Mendoza, Maria A; Raja, Mohammed A; Rosello, Gemma; Anjan, Shweta; Simkins, Jacques; Camargo, Jose F; Morris, Michele I; Sinha, Neeraj; Guerra, Giselle; Abbo, Lilian M; Abbo, Lilian M; Natori, Yoichiro
Abstract: Background: Community acquired respiratory virus infections (RVI) are a major concern in solid organ transplant (SOT) recipients due to severe complications such as lower respiratory tract infection (LRTI), superimposed fungal and bacterial pneumonia, intensive care admission and mortality. Besides influenza and respiratory syncytial virus (RSV), there is paucity of data of RVI in SOT recipients. Table 1: Patients characteristics Table 2: Concomitant infections Methods: Retrospective cohort study of a single large transplant center was performed. Data of multiplex qualitative PCR-based respiratory viral panel (RVP) samples collected between January 2017 and December 2019 were included. It is important to mention that our institution generally performs the RSV/influenza rapid detection assay as an initial test; if negative, the multiplex PCR panel is usually done. We did not include results from the RSV/influenza rapid test in this study. Results: One hundred transplant patients with a single positive RVP were included (table 1). Transplanted organs include kidney (40%), followed by lung (33%) and liver (9%). Most common presenting symptoms were cough (52%), shortness of breath (28%) and rhinorrhea (26%). Of note fever was seen in only 24%. Most common RVI was Rhinovirus/Enterovirus (RHV/ENT) (59%), followed by non-SARS-CoV-2 Coronavirus (19%) and Parainfluenza (PIV) (14%). None of the patients had neutropenia, however, 52% had lymphocytopenia. Lung transplant patients developed LRTI in 70% of cases compared to non-lung transplant 64% (p=0.412). Multivariate analysis showed patients with PIV 3 were less likely to develop LRTI (p= 0.038). Significant Cytomegalovirus DNAemia (>137 IU/mL) was noted in 9.8% of the recipients. No proven or probable pulmonary fungal infection were noted within 3 months after diagnosis of RVI. Five patients were admitted to the Intensive care unit due to septic shock. Three patients died at 4, 5 and 35 days after diagnosis of RHV/ENT, PIV-3 and RHV/ENT respectively. Conclusion: Most of the cases of RVI were due to RHV/ENT. Patients with PIV 3 were less likely to develop LRTI. Lung transplant recipients developed LRTI with similar incidence to non-lung recipients. Our data shows a very low mortality of 3% after RVI in our SOT cohort, which warrants larger studies. Disclosures: Michele I. Morris, MD, Viracor Eurofins (Advisor or Review Panel member)